2011
DOI: 10.1007/s11920-011-0211-5
|View full text |Cite
|
Sign up to set email alerts
|

Updates on Attention-Deficit/Hyperactivity Disorder and Learning Disorders

Abstract: The relationship of attention-deficit/hyperactivity disorder (ADHD) to learning disorders was reviewed and included reading disability, mathematics learning disability, and nonverbal learning disability. Genetic, neuroimaging, and neuropsychological functioning were examined for each disorder, along with a discussion of any existing literature when ADHD co-occurred with the disorder. All the disorders were found to frequently co-occur with ADHD. A review of the underlying neuroanatomic and neurofunctional data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…Growing evidence suggests that inattention is more closely related to mathematical skill deficits, since MD occurs more frequently in children who demonstrate inattentive symptoms and combined types of ADHD [19]. However, some purported that children with MD demonstrate failure with automatization (i.e., retrieval of basic math facts), which results from a deficit in visuospatial or numerical working memory and processing speed [20]. Capano et al [10] compared four groups of children with ADHD and other groups with SLD (ADHD, ADHD + RD, ADHD + MD, and ADHD + MD + RD) and found that although children with comorbid ADHD and MD exhibited poor arithmetic skills overall, they exhibited stronger receptive and expressive language performance compared to the comorbid ADHD, MD, and RD groups.…”
Section: Shared Neuropsychological Factorsmentioning
confidence: 99%
“…Growing evidence suggests that inattention is more closely related to mathematical skill deficits, since MD occurs more frequently in children who demonstrate inattentive symptoms and combined types of ADHD [19]. However, some purported that children with MD demonstrate failure with automatization (i.e., retrieval of basic math facts), which results from a deficit in visuospatial or numerical working memory and processing speed [20]. Capano et al [10] compared four groups of children with ADHD and other groups with SLD (ADHD, ADHD + RD, ADHD + MD, and ADHD + MD + RD) and found that although children with comorbid ADHD and MD exhibited poor arithmetic skills overall, they exhibited stronger receptive and expressive language performance compared to the comorbid ADHD, MD, and RD groups.…”
Section: Shared Neuropsychological Factorsmentioning
confidence: 99%
“…Neuroimaging studies have suggested similar neurodevelopmental differences in the caudate, cerebellum, corpus callosum, and neurobiological dysfunction in children with ADHD and learning disorders, both comorbid and alone. 49 For example, implicit sequence learning, a cognitive process mediated by frontal-striatal-cerebellar circuitry appears to be atypical in children with ADHD. 50 The presence of comorbid learning disorders can be confirmed with psychological testing and a review of the patient's academic history.…”
Section: Learning Disordersmentioning
confidence: 99%
“…The rational for this is based on the effectiveness design of the study. The majority of the children with ADHD presents with comorbid disorders (Kadesjö et al, 2003; Willcutt et al, 2005; Gadow et al, 2006; Jakobson and Kikas, 2007; Anney et al, 2008; Semrud-Clikeman and Bledsoe, 2011; Stein et al, 2011; Vakil et al, 2012), and parents and children seeking help in our outpatient clinic request treatment of all impairing problems, and not just ADHD (please refert to the preliminary result section for information on comorbidities). The children under stimulant medication are also not excluded from the study, but dose and possible changes will be recorded.…”
Section: Methodsmentioning
confidence: 99%